A comprehensive role evaluation and mechanism exploration of POGLUT2 in pan-cancer - Xu, Xianyun; Xie, Guangming; Xie, Mingfeng; Liu, Qian (Frontiers in Oncology, 2022)
Objective To evaluate the role of POGLUT2 in pan-cancer through bioinformatics analysis and experimental verification. Methods Expression, gene mutation and amplification, methylation, and copy number alteration (CNA) of POGLUT2 were evaluated using The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedia (CCLE), and Genotype-Tissue Expression (GTEx) databases. Moreover, POGLUT2 on survival and disease progression in pan-cancer was performed using TCGA data. Immune infiltration and tumor microenvironment evaluations were assessed by ImmuneScore, ImmuCellAI, and TIMER databases. POGLUT2 correlated drug resistance analysis was performed using the GDSC2 database. Furthermore, POGLUT2 knockdown of breast cancer cells was established, followed by in vitro biological function assays and in vivo tumor growth study. The mechanisms of POGLUT2 in breast cancer were briefly evaluated via its connection with Notch signaling. Results Increased levels of POGLUT2 were found in multiple types of cancer tissues and cell lines. Moreover, increased gene mutation and amplification, methylation, and CNA of POGLUT2 were found in several types of cancers. POGLUT2 was mainly expressed in stromal cells as verified by StromalScore, ESTIMATEScore, ImmuneScore, and Tumor purity, and POGLUT2 was positively correlated with cancer-associated fibroblasts, macrophages, monocytes, and neutrophils in the tumor microenvironment. In vitro and in vivo results showed that POGLUT2 knockdown could delay tumor growth and progression. Notch signaling components were related to the function of POGLUT2. Conclusions Increased levels of POGLUT2 could result in the dysregulated immune cell infiltration and tumor microenvironment and showed a significant regulatory effect on the progression of breast cancer through Notch-related signaling.